S.Y Agnon and His Image as a Genius - Weiss, Haim (MiKAN, 2022)
Many times and on various occasions, S.Y. Agnon has been perceived as a genius, an extraordinary writer with an unprecedented command of an enormous variety ׳ of sources from Jewish tradition. Readers and critics alike perceive him as an anomalous phenomenon among the Hebrew writers of his generation. His character has been portrayed as one who worked tirelessly in his small chamber, surrounded by thousands of books from all branches of Hebrew literature. This article does not seek to join the academic discourse that examines the true scope of his knowledge, nor to offer a new perspective on his virtuoso ability to make literary use of Jewish sources. Rather, it seeks to examine the significance of Agnon’s definition as a genius and the role of his actual and imagined library in shaping the discourse dedicated to him and his work.